Movement patterns of individual migrating western rock lobster, Panulirus cygnus, in Western Australia - Smith, Roy; Beale, N. (The Royal Society of New Zealand, 2009)
Migrating and pre‐migrating western rock lobster Panulirus cygnus were tagged with datastorage tags that recorded temperature and pressure, which was converted to depth (Pressure (kPa) — surface pressure (kPa)/10)) at Dongara and Jurien Bay in Western Australia between December 2005 and December 2007. All lobsters were fitted with tag flotation devices, and returns were made by either commercial fishers or beachcombers who located detached tags. A total of 135 lobsters were released with “backpack” flotation tags, but only 84 (62.2%) of the backpacks carried data‐storage tags. Depths of release ranged from 5 to 113 m. Of the tagged lobsters released, commercial fishers recaptured 52 (38.5%), whereas 11 tags (8.1%) were found by beachcombers. At least 33%, and possibly up to 63%, of animals identified by their pale coloration as pre‐migrating individuals, failed to migrate. Those that did migrate (n = 11) were at liberty from 1 to 94 days and showed generally similar movement patterns in that they migrated only at night from darkness (after 2000 h) until after moonrise. However, their movement patterns were less constrained by the rising of the moon in deep water. Only 27% migrated nightly, compared with 73% that skipped migrating on one or more nights, to restart some days later. This latter proportion would likely have been considerably greater, but some migrating animals were only at large for short periods before recapture, and therefore had little time to show any variation to the nocturnal migration pattern. Individual speeds of migration during periods of activity were estimated for nine lobsters as 0.20 to 0.68 km h−1, with a mean speed of 0.44 km h−1, or 7.4 m min−1. Improved knowledge of daily movement patterns resulting from this study provides a potentially important input into technological improvements in bait and pot design.